Effect of different sweetener and concentration on sensory and chemical attributes of peeled and un-peeled coffee kombucha - Fibrianto, Kiki; Aunura, Fadila Artameivia (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
The exocarp and mesocarp of the coffee bean are traditionally not peeled in some regions of Indonesia when producing coffee using traditional methods. Even though it has been a long practice among traditional coffee farmers, unpeeled coffee has a very limited market due to its sensory weakness and thus hardly meets international coffee standards. Therefore, product diversification can be a strategic approach to improving this sub-grade coffee’s economic value. One of the alternatives is developing the coffee into kombucha. Kombucha processing has been well known for its ability to transform non-delightful sensory attributes into something more acceptable. In this study, the effects of different sweeteners and concentrations were investigated and designed as a nested experiment. Both peeled and unpeeled coffee were brewed with the French-press technique and used as a medium for kombucha. Different sweeteners, such as sucrose, glucose, and a mixture of sucrose and honey, were also applied in ratios of 5, 10, and 15%. It was observed that both peeled and unpeeled coffee kombucha have a competitive level of sensory preference with similar total sugar, total acidity, and total dissolved solids (p-value > 0.05). Those were achieved by adding 15% sucrose for peeled coffee kombucha and 10% sucrose-honey mix for the unpeeled one.